Composite sheet, inner container, cooking utensil and manufacturing method of composite sheet

By arranging a micron-level concave-convex structure on the surface of the metal substrate and attaching a columnar nanocrystal PVD coating, the problem of insufficient non-stickiness and easy cleaning of the composite sheet when used at high temperatures is solved, and high hardness and scratch resistance are achieved.

CN119332203APending Publication Date: 2025-01-21ZHEJIANG SUPOR ELECTRICAL APPLIANCES MFG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310882064.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When existing composite sheets are used at high temperatures, traditional non-stick coatings may release harmful substances, and have low hardness and poor bonding power, resulting in insufficient non-stickness and easy cleaning.

Method used

A spaced micron-level concave-convex structure is set on the surface of the metal substrate, and a columnar nanocrystalline PVD coating is attached through physical vapor deposition to form a composite sheet.

Benefits of technology

The composite sheet is realized to have good non-stick, hydrophobic and easy-to-clean properties without providing a special non-stick coating, and at the same time, the hardness and scratch resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332203A_ABST
    Figure CN119332203A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sheet, an inner container, a cooking utensil and a manufacturing method of the composite sheet. The composite sheet comprises a metal matrix and a coating film. The surface of the metal base body is provided with a plurality of concave-convex structures which are arranged at intervals, and the concave-convex structures are convex or concave. The coating film is attached to the surface of the metal matrix through physical vapor deposition and covers the concave-convex structure, the coating film comprises a surface layer, and the surface layer is a columnar nanocrystal structure layer grown through physical vapor deposition. According to the application, the micron-sized concave-convex structure and the columnar nanocrystal PVD coating film are matched, so that the composite sheet has the characteristics of good non-stick property, hydrophobic property and easiness in cleaning on the basis of not arranging a special non-stick coating, and also has the effects of high hardness and scratch resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a composite sheet, an inner pot, a cooking utensil, and a method for manufacturing the composite sheet. Background Art

[0002] In order to make the composite sheet easy to clean and extend its service life, an adhesive coating is usually used. Common coating materials include fluororesin non-stick coating and ceramic coating, among which the non-stick coating has excellent non-stick and corrosion resistance, but low hardness, poor bonding with the substrate, easy to fall off, and may release harmful substances such as PFOA (perfluorooctanoic acid) at high temperatures, while the ceramic non-stick coating has poor water resistance and deteriorates in non-stick properties after long-term use. Therefore, hard PVD (physical vapor deposition) coating is currently used to replace the traditional liner coating, but due to the mismatch between the substrate surface structure and the PVD coating, its hydrophobic performance is poor, which cannot meet the user's requirements for easy cleaning performance, and often causes problems such as sticking to the pan and difficult cleaning.

[0003] Therefore, a composite sheet, an inner pot, a cooking utensil and a method for manufacturing the composite sheet are needed to at least partially solve the above problems. Summary of the invention

[0004] A series of simplified concepts are introduced in the content section of this application, which will be further described in detail in the detailed implementation section. The content section of this application does not mean to attempt to define the key features and essential technical features of the technical solution claimed for protection, nor does it mean to attempt to determine the scope of protection of the technical solution claimed for protection.

[0005] In order to at least partially solve the above problems, the first aspect of the present application provides a composite sheet, comprising:

[0006] A metal substrate, wherein the surface of the metal substrate has a plurality of concave-convex structures arranged at intervals, wherein the concave-convex structures are convexities or concavities;

[0007] The coating is attached to the surface of the metal substrate by physical vapor deposition and covers the concave-convex structure, wherein the coating comprises a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.

[0008] According to the present application, the combination of the micron-scale concave-convex structure and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also have high hardness and scratch resistance.

[0009] Preferably, the plurality of concave-convex structures are uniformly arranged at a first preset distance along a first direction, and the plurality of concave-convex structures are uniformly arranged at a first preset distance along a second direction perpendicular to the first direction, so as to form a concave-convex structure array.

[0010] According to the present application, the manufacturing process is simpler, the production cost is reduced, the coordination effect with the coating is better, and the non-stick and easy-to-clean properties are further improved.

[0011] Preferably, the plurality of concave-convex structures are arranged into concave-convex units with a specific shape, the plurality of concave-convex units are uniformly arranged at a second preset distance along a first direction, and the plurality of concave-convex units are uniformly arranged at a second preset distance along a second direction perpendicular to the first direction to form a concave-convex unit array.

[0012] According to the present application, the manufacturing process is simpler, the production cost is reduced, the coordination effect with the coating is better, and the non-stick and easy-to-clean properties are further improved.

[0013] Preferably, the specific shape of the concave-convex unit is a solid shape composed of a plurality of concave-convex structures evenly arranged at a first preset distance; or

[0014] The specific shape of the concave-convex unit is configured as a hollow shape formed by a plurality of concave-convex structures being evenly arranged at a first preset distance.

[0015] According to the present application, the manufacturing process is simpler, the production cost is reduced, the coordination effect with the coating is better, and the non-stick and easy-to-clean properties are further improved.

[0016] Preferably, the second preset distance is greater than the first preset distance.

[0017] According to the present application, the manufacturing process is simpler, the production cost is reduced, the coordination effect with the coating is better, and the non-stick and easy-to-clean properties are further improved.

[0018] Preferably, the surface roughness of the surface layer is 0.1-3 μm, and the surface roughness of the metal substrate is 0.1-3 μm; and / or

[0019] The friction coefficient of the surface layer is 0.05-0.4, and the contact angle of water on the surface of the surface layer is 80-110°.

[0020] According to the present application, a PVD coating is provided on the surface of a metal substrate having a micron-scale concave-convex structure and having a relatively smooth property, so that the coating surface covering the concave-convex structure and the surface outside the concave-convex structure also has a smooth property, thereby forming a smooth composite micro-nano structure, further improving the non-stickiness and easy-cleaning properties of the composite sheet; the larger hydrophobic angle makes the surface energy of the coating lower, further improving the non-stickiness and easy-cleaning properties of the composite sheet.

[0021] Preferably, the radial dimension of the concavo-convex structure is 10-100 μm; and / or

[0022] The height dimension of the concavo-convex structure is 5-50 μm.

[0023] According to the present application, the metal substrate and the coating film cooperate better, further improving the non-stickiness and easy-to-clean properties of the composite sheet.

[0024] Preferably, the columnar nanocrystal structure in the surface layer has a plurality of crystal grains growing in a columnar shape, and the side surfaces of the plurality of crystal grains are bonded to each other. When the surface layer is at a predetermined thickness, the top ends of the crystal grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.

[0025] According to the present application, the nano-scale concave-convex structure formed on the coating surface cooperates with the concave-convex structure on the metal substrate surface to form a micro-nano double concave-convex structure, further improving the non-stickiness and easy-to-clean performance of the composite sheet.

[0026] Preferably, the radial size of the grains is 20-80 nm; and / or

[0027] The predetermined thickness of the surface layer is 100-600 nm.

[0028] According to the present application, a nanoscale dimension can be provided for the surface of the coating to form a special columnar nanocrystal structure.

[0029] Preferably, the first preset distance is 10-1000 μm.

[0030] According to the present application, the arrangement of the concave-convex structure is more reasonable, the coordination effect between the metal substrate and the coating is better, and the non-stickiness and easy-cleaning properties of the composite sheet are further improved.

[0031] Preferably, the coating further includes a transition layer, the surface layer is attached to the transition layer, the transition layer includes a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked.

[0032] According to the present application, the growth of the surface layer on the transition layer can improve the density of the surface layer, thereby improving the hardness and corrosion resistance.

[0033] Preferably, the coating further comprises a bottom layer, the bottom layer is attached to the surface of the metal substrate, the transition layer is attached to the bottom layer, and the bottom layer is a metal layer.

[0034] According to the present application, the metal bottom layer can increase the bonding force between the coating and the metal substrate, making it difficult for the coating to fall off from the metal substrate, thereby increasing the service life.

[0035] Preferably, the thickness of the first transition layer is 10-50 nm, the thickness of the second transition layer is 10-50 nm, and the total thickness of the transition layers is 300-1000 nm; and / or

[0036] The thickness of the bottom layer is 100-500 nm; and / or

[0037] The total thickness of the coating is 700-2000nm.

[0038] According to the present application, the thickness of each layer is reasonably set, which further improves the adhesion and surface performance of the coating.

[0039] Preferably, the surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.

[0040] According to the present application, the specific surface layer material can enable the surface layer to grow into columnar nanocrystals, further improving the non-stickiness and easy-to-clean properties of the composite sheet.

[0041] Preferably, the surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer.

[0042] According to the present application, since copper does not react with carbon and nitrogen elements, nor can it form a solid solution with carbonitrides, but exists in an amorphous form, adding copper elements to the surface layer can effectively reduce the surface energy and further improve the non-stickiness and easy-to-clean properties of the composite sheet.

[0043] Preferably, amorphous copper is coated outside the grains of the columnar nanocrystalline structure.

[0044] According to the present application, copper can inhibit the growth of crystal grains, so the crystal grains will be smaller, effectively reducing the surface energy, and further improving the non-stickiness and easy-to-clean properties of the composite sheet.

[0045] Preferably, the first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;

[0046] The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;

[0047] The second transition layer is different from the first transition layer.

[0048] According to the present application, a transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of columnar nanocrystalline structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer, forming a fine and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer increases, its hardness and corrosion resistance are also improved.

[0049] Preferably, the bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.

[0050] According to the present application, the metal base layer and the transition layer contain the same metal element, which can increase the bonding strength between the base layer and the transition layer and further increase the service life.

[0051] A second aspect of the present application provides an inner liner, which includes the composite sheet according to any one of the above technical solutions.

[0052] According to the present application, the inner liner is made of the above-mentioned composite sheet. The combination of the micron-scale concave-convex structure and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also has high hardness and scratch resistance.

[0053] A third aspect of the present application provides a cooking utensil, comprising:

[0054] A pot body, wherein the pot body is provided with the inner pot according to the above technical solution;

[0055] The cover body is openably and closably arranged on the pot body. When the cover body covers the pot body, a cooking space is formed between the cover body and the inner pot.

[0056] According to the present application, the cooking utensil includes the above-mentioned inner pot, and the combination of the micron-scale concave-convex structure and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also has high hardness and scratch resistance.

[0057] A fourth aspect of the present application provides a method for manufacturing a composite sheet, the method comprising:

[0058] The step of preparing a metal substrate comprises:

[0059] The step of forming a concavo-convex structure is as follows: a plurality of concavo-convex structures are prepared on the surface of the metal substrate and are arranged at intervals, wherein the concavo-convex structures are convex or concave.

[0060] placing the metal substrate in a physical vapor deposition apparatus;

[0061] The physical vapor deposition step is to deposit a coating at least on the concave-convex structure of the metal substrate, and the physical vapor deposition step includes a surface deposition step: the surface layer of the coating is grown into a columnar nanocrystalline structure by physical vapor deposition.

[0062] According to the present application, the combination of the micron-scale concave-convex structure of the composite sheet prepared by this manufacturing method and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick properties, hydrophobic properties and easy-to-clean characteristics without setting a special non-stick coating, and also have high hardness and scratch resistance. The columnar nanocrystal structure can be directly formed on the surface of the metal substrate through physical vapor deposition without the need for additional steps.

[0063] Preferably, the concave-convex structure is prepared by a rolling process, a roll-to-roll micro-imprinting process, a chemical etching process, a laser etching process or an ultraviolet lithography process.

[0064] According to the present application, the concave-convex structure can be prepared by a variety of processes, so that the manufacturing method selection is more diverse.

[0065] Preferably, the step of forming the concave-convex structure further comprises: using the laser etching process to prepare the concave-convex structure on the surface of the metal substrate, setting the laser power density to 10 6 -10 7 W / cm 2 , the laser spot size is 10-100μm, the scanning speed is 5-20mm / s, and the pulse frequency is 10-100KHz.

[0066] According to the present application, the concave-convex structure is prepared by laser etching process, which makes the process simpler and the control more precise, and the prepared concave-convex structure cooperates better with the coating.

[0067] Preferably, the step of preparing the metal substrate further comprises a polishing step after the step of forming the concavo-convex structure, wherein the metal substrate is polished so that the surface roughness of the metal substrate is 0.1-3 μm.

[0068] According to the present application, the surface roughness of the metal substrate can be reduced by polishing, thereby reducing the surface roughness of the surface layer, so that the metal substrate and the coating form a smooth composite micro-nano structure, further improving the non-stickiness and easy-to-clean properties.

[0069] Preferably, the metal substrate is polished by a plasma polishing process, a magnetic fluid polishing process or a chemical polishing process.

[0070] According to the present application, a more reasonable polishing process can be used to polish the concave-convex structure with a smaller size on the surface of the metal substrate.

[0071] Preferably, the polishing step comprises: polishing the concave-convex structure using the plasma polishing process, setting the density of the plasma to 1×10 11 -5×10 11 cm 3 , polishing power is 50-200W, gas flow rate is 10-50sccm, and polishing time is 5-30min.

[0072] According to the present application, a more reasonable polishing process is selected, the process parameter control is simpler, and the polishing effect is better.

[0073] Preferably, a deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source;

[0074] The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis;

[0075] The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening the carbon source and the nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.

[0076] According to the present application, a columnar nanocrystalline surface layer of carbonitride can be grown on the surface of a metal substrate through a PVD process.

[0077] Preferably, the physical vapor deposition step also includes a transition layer deposition step, and the transition layer deposition step is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form a first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form a second transition layer.

[0078] According to the present application, a transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of a columnar nanocrystal structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer, forming a fine and dense columnar nanocrystal structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer increases, its hardness and corrosion resistance are also improved; by rotating the metal substrate to be alternately covered by the coating material produced by the first metal target and the second metal target, an alternating first transition layer and a second transition layer can be efficiently formed.

[0079] Preferably, the physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step, and the bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.

[0080] According to the present application, the metal base layer can be deposited using the same PVD equipment, and the metal base layer can increase the bonding strength between the coating and the metal substrate, making the coating less likely to fall off the metal substrate, thereby increasing the service life.

[0081] Preferably, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;

[0082] The step of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to 100-600nm.

[0083] According to the present application, a more reasonable process parameter setting can obtain a surface layer with a specific thickness, further improving the hardness, bonding strength and ease of cleaning of the coating.

[0084] Preferably, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;

[0085] The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to 300-1000nm.

[0086] According to the present application, the process parameters are set more reasonably, further improving the hardness, bonding strength and easy cleaning of the coating.

[0087] Preferably, the deposited bottom layer also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to 100-500nm.

[0088] According to the present application, the process parameters are set more reasonably, further improving the hardness, bonding strength and easy cleaning of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] The following drawings of the present application are used as a part of the present application for understanding the present application. The drawings show the implementation modes of the present application and the description thereof, and are used to explain the principle of the present application.

[0090] In the attached figure:

[0091] Figure 1 It is a partial cross-sectional schematic diagram of a composite sheet according to a preferred embodiment of the present application;

[0092] Figure 2 is a partial cross-sectional schematic diagram of a composite sheet according to another embodiment of the present application;

[0093] Figure 3 for Figure 1 A partial enlarged schematic diagram of a composite sheet;

[0094] Figure 4 for Figure 2 A partial enlarged schematic diagram of a composite sheet;

[0095] Figure 5 for Figure 1 A schematic top view of a composite sheet;

[0096] Figure 6 for Figure 2 A schematic top view of a composite sheet;

[0097] Figure 7 It is a schematic cross-sectional view of the composite sheet material according to the present application in the non-concave-convex structure area;

[0098] Figure 8 A more detailed schematic cross-sectional structure diagram of a coating of a composite sheet according to an embodiment of the present application;

[0099] Figure 9a-9d It is a schematic diagram of the cross-sectional structure of the surface layer of the coating according to the present application at different growth thicknesses;

[0100] Fig.10 is a top cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;

[0101] Fig.11 is a side cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;

[0102] Fig.12 A simplified flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application;

[0103] Fig.13 A more detailed schematic flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application.

[0104] Description of reference numerals:

[0105] 110: Metal matrix

[0106] 111: Concave and convex structure

[0107] 112: Concave and convex unit

[0108] 120: Surface

[0109] 121: Grain

[0110] 122: Protrusion

[0111] 130: Transition layer

[0112] 131: First transition layer

[0113] 132: Second transition layer

[0114] 140: Bottom

[0115] 150: Coating

[0116] 10: Physical vapor deposition equipment

[0117] 11: Deposition furnace

[0118] 12: Rotating stand

[0119] 13: The first metal target

[0120] 14: Second metal target DETAILED DESCRIPTION

[0121] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is apparent to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features well known in the art are not described.

[0122] In order to thoroughly understand the present application, a detailed description will be provided in the following description. Obviously, the implementation of the embodiments of the present application is not limited to the specific details familiar to those skilled in the art. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other embodiments.

[0123] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of the features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or combinations thereof.

[0124] Ordinal numbers such as “first” and “second” cited in the present application are merely identifications and do not have any other meanings, such as a specific order, etc. Moreover, for example, the term “first component” itself does not imply the existence of the “second component”, and the term “second component” itself does not imply the existence of the “first component”.

[0125] It should be noted that the terms "upper", "lower", "front", "back", "left", "right", "inside", "outside" and similar expressions used in this document are for illustrative purposes only and are not limiting.

[0126] Now, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in a variety of different forms and should not be interpreted as being limited to the embodiments described herein. It should be understood that these embodiments are provided to make the disclosure of the present application thorough and complete, and to fully convey the concepts of these exemplary embodiments to those of ordinary skill in the art.

[0127] The first aspect of the present application provides a composite sheet, such as Figure 1 and Figure 2As shown, the composite sheet includes a metal substrate 110 and a coating 150. The surface of the metal substrate 110 has a plurality of concave-convex structures 111 arranged at intervals, and the concave-convex structures 111 are protrusions or depressions. The coating 150 is attached to the surface of the metal substrate 110 by physical vapor deposition and covers the concave-convex structure 111, wherein the coating 150 includes a surface layer 120, and the surface layer 120 is constructed as a columnar nanocrystalline structure layer grown by physical vapor deposition. Preferably, the columnar nanocrystalline structure in the surface layer 120 has a plurality of crystal grains 121 grown in a columnar shape, and the side surfaces of the plurality of crystal grains 121 are attached to each other, and the radial dimension D of the crystal grains 121 is 20-80nm. According to this solution, a nanoscale dimension can be provided for the surface of the coating 150 to form a special columnar nanocrystalline structure.

[0128] According to the present application, the combination of the micron-scale concave-convex structure and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick, hydrophobic and easy-to-clean properties without setting a special non-stick coating, and also have high hardness and scratch resistance.

[0129] The above-mentioned nanoscale refers to a scale ranging from 1 to 100 nm.

[0130] Preferably, the metal substrate 110 can be made of stainless steel, aluminum alloy, titanium alloy, etc. For example, in one embodiment, the metal substrate 110 is made of a composite material of a 304 stainless steel layer and a low carbon steel layer, wherein the thickness of the stainless steel layer is greater than 0.1 mm, and the total thickness of the metal substrate 110 is greater than 1 mm.

[0131] The surface roughness of the metal substrate 110 is 0.1-3 μm. The surface of the metal substrate 110 is provided with a concave-convex structure 111, but still has a relatively low surface roughness, so that the metal substrate 110 has a smooth surface, and the cooperation effect with the coating 150 is better, further improving the non-stickiness and easy-to-clean performance of the composite sheet.

[0132] Specifically, Figure 5 As shown, in one embodiment, a plurality of concave-convex structures 111 are uniformly arranged at a first preset distance along a first direction, and a plurality of concave-convex structures 111 are uniformly arranged at a first preset distance along a second direction perpendicular to the first direction, so as to form an array of concave-convex structures 111. In other words, the spacing between adjacent concave-convex structures 111 along the first direction and the second direction is the same, and the plurality of concave-convex structures 111 are uniformly arranged.

[0133] like Figure 6As shown, in another embodiment, a plurality of concave-convex structures 111 are arranged into a concave-convex unit 112 having a specific shape, and the plurality of concave-convex units 112 are uniformly arranged at a second preset distance along a first direction, and the plurality of concave-convex units 112 are uniformly arranged at a second preset distance along a second direction perpendicular to the first direction to form an array of concave-convex units 112. In other words, each concave-convex unit 112 includes a plurality of concave-convex structures 111, and the spacing between adjacent concave-convex units 112 along the first direction and the second direction is the same, and the plurality of concave-convex units 112 are uniformly arranged. Further, the specific shape of the concave-convex unit 112 can be constructed as a solid shape composed of a plurality of concave-convex structures 111 uniformly arranged at a first preset distance. The specific shape of the concave-convex unit 112 can also be constructed as a hollow shape surrounded by a plurality of concave-convex structures 111 uniformly arranged at a first preset distance. For example, Figure 6 The specific shape of the concave-convex unit 112 is a hollow square composed of a plurality of concave-convex structures 111 arranged evenly at a first preset distance. It should be understood that the specific shape of the concave-convex unit 112 can also be configured as other shapes such as a rectangle or a circle. In this embodiment, the second preset distance is greater than the first preset distance, that is, the spacing between the concave-convex units 112 is greater than the spacing between the concave-convex structures 111 in the concave-convex unit 112.

[0134] More specifically, the first preset distance is 10-1000 μm, the radial dimension of the concave-convex structure 111 is 10-100 μm, and the height dimension of the concave-convex structure 111 is 5-50 μm.

[0135] The surface layer 120 has a low surface energy characteristic, and the contact angle of water on the surface of the surface layer 120 is 80-110°.

[0136] Preferably, the surface layer 120 may be a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. The specific surface layer material can enable the surface layer 120 to grow into columnar nanocrystals, further improving the non-stickiness and easy-to-clean properties of the composite sheet. Figure 3 and Figure 4 As shown, the thickness of the surface layer 120 is preferably set to 100-600nm. When the thickness of the surface layer 120 is within the above-mentioned predetermined thickness range, a protrusion 122 can grow on the top of the grain 121, so that a nano-scale concave-convex structure is formed on the surface of the surface layer 120. More preferably, the thickness of the surface layer 120 is preferably set to 300-500nm.

[0137] refer to Figure 9a-9d The cross-sectional morphology of the surface layer 120 at different growth thicknesses is shown. Figure 9a The cross-sectional morphology is shown when the thickness of the surface layer 120 is 50 nm. Figure 9b The cross-sectional morphology when the thickness of the surface layer 120 is 100 nm is shown. Fig.9cThe cross-sectional morphology is shown when the thickness of the surface layer 120 is 400 nm. Figure 9d The cross-sectional morphology when the thickness of the surface layer 120 is 600nm is shown. It can be seen from the figure that when the thickness of the surface layer 120 is 50nm, the top of the grain 121 cannot grow a protrusion 122, and the surface of the surface layer 120 forms a flat surface. As the deposition thickness of the surface layer 120 increases, when the thickness is greater than 100nm as shown in the figure, the top of the grain 121 gradually grows a protrusion 122, and the protrusion 122 becomes more obvious and fuller as the deposition thickness increases. However, when the deposition thickness of the surface layer 120 increases from 400nm to 600nm, the protrusion 122 at the top of the grain 121 tends to be flattened. It can be seen that when the deposition thickness of the surface layer 120 exceeds 600nm, the protrusion 122 at the top of the grain 121 continues to be flattened, which will make the concave-convex structure less obvious.

[0138] Further preferably, copper element can be added to the surface layer 120 to further improve the non-stick performance. For example, the surface layer 120 is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer. Since copper does not react with carbon and nitrogen elements, and cannot form a solid solution with carbonitride, but exists in an amorphous form, during the physical vapor deposition process, the amorphous copper is coated outside the columnar nanocrystalline structure of the grain 121, inhibiting the growth of the grain 121, so that the grain 121 will be smaller, effectively reducing the surface energy, and further improving the non-stick and easy-to-clean performance of the composite sheet.

[0139] The coating 150 is provided on the surface of the metal substrate 110 with a relatively smooth micron-scale concavo-convex structure 111, so that the coating surface layer 120 covering the concavo-convex structure 111 and the portion outside the concavo-convex structure 111 also has a smooth property, the surface roughness of the surface layer 120 is 0.1-3 μm, and the friction coefficient of the surface layer 120 is 0.05-0.4. Thus, a smooth composite micro-nano structure is formed, and the lower the surface roughness and the smoother it is, the better its non-stickiness is.

[0140] Preferably, if Figure 7 and Figure 8As shown, the coating 150 also includes a transition layer 130, the surface layer 120 is attached to the transition layer 130, and the above-mentioned grains 121 grow in a direction perpendicular to the surface of the transition layer 130. The transition layer 130 includes a first transition layer 131 and a second transition layer 132, and the first transition layer 131 and the second transition layer 132 are alternately stacked. Among them, the first transition layer 131 is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer. The second transition layer 132 is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer. The second transition layer 132 is different from the first transition layer 131. The thickness of the first transition layer 131 and the second transition layer 132 are both 10-50nm, and the total thickness of the transition layer 130 is 300-1000nm.

[0141] The transition layer 130, which is an alternating arrangement of two material layers formed by titanium, chromium and zirconium base and their compounds, can produce a template effect on the growth of the columnar nanocrystalline structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals in the surface layer 120, and making the columnar grains 121 tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer 120 and forming a fine and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer 120 increases, its hardness and corrosion resistance are also improved.

[0142] Further preferably, the coating 150 further includes a bottom layer 140, the bottom layer 140 is attached to the surface of the metal substrate 110, the transition layer 130 is attached to the bottom layer 140, and the bottom layer 140 is a metal layer. The bottom layer 140 is preferably a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer. The thickness of the bottom layer 140 is 100-500nm. Thus, the metal bottom layer 140 can increase the bonding force between the coating 150 and the metal substrate 110, so that the coating 150 is not easy to fall off from the metal substrate 110, thereby increasing the service life.

[0143] Preferably, the total thickness of the coating 150 including the surface layer 120, the transition layer 130 and the bottom layer 140 is 700-2000nm, preferably 800-1600nm. Further preferably, the total thickness of the coating 150 is 1100-1300nm. Referring to Table 1, the performance test of embodiments with different thicknesses of the coating 150 is shown. Among them, the experimental steps of the easy-to-clean performance of rice are as follows: (1) Add rice and water according to the type and volume of different cooking utensils; (2) Turn on the power to cook, and keep warm for 10 minutes after the cooking is completed; (3) Invert the cooking utensil and observe whether all the rice falls off by gravity or gently shaking the inner pot; (4) After cleaning the cooking utensil, repeat the above experiment for a total of 5 times to check the easy-to-clean performance of the cooking utensil, and determine the evaluation level of the rice residue according to the average weight of the residue in the last 4 times. The evaluation standards for the ease of cleaning of rice are as follows: Level 1: Lightly shake the cooking utensil or without shaking, and all the rice can fall off the utensil; Level 2: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is ≤50g; Level 3: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is 50g<rice weight≤100g; Level 4: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is>100g.

[0144] Table 1

[0145]

[0146]

[0147] The hardness of the coating 150 increases with the increase of the total thickness, while the bonding force between the coating 150 and the metal substrate 110 increases first and then decreases with the thickness, especially when the total thickness is greater than 2000 nm, the bonding force drops sharply.

[0148] For example, as a first optional embodiment, the surface layer 120 is a titanium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a titanium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-titanium composite metal layer. As a second optional embodiment, the surface layer 120 is a zirconium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-zirconium composite metal layer. As a third optional embodiment, the surface layer 120 is a chromium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a titanium carbonitride layer, and the bottom layer 140 is a titanium-zirconium composite metal layer.

[0149] In order to further improve the bonding force between the surface layer 120 and the transition layer 130, the surface layer 120 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the surface layer 120 contain the same carbon nitride compound, for example, refer to the first optional embodiment and the second optional embodiment described above. In order to further improve the bonding force between the transition layer 130 and the bottom layer 140, the bottom layer 140 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the bottom layer 140 contain the same metal element, for example, refer to the first optional embodiment and the third optional embodiment described above.

[0150] The optional combination of each layer can also be: as a fourth optional embodiment, the surface layer 120 adopts a titanium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a fifth optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a sixth optional embodiment, the surface layer 120 adopts a zirconium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-zirconium composite metal layer. As a seventh optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a titanium carbonitride layer, respectively, and the bottom layer 140 adopts a titanium-zirconium composite metal layer.

[0151] The second aspect of the present application also provides an inner pot, which is made of the composite sheet of the first aspect. The inner pot has a concave-convex structure 111 and a coating 150 at least at the bottom of the inner surface in contact with the food. Preferably, the inner surface of the inner pot has the concave-convex structure 111 and the coating 150, so that the surface layer 120 of the coating 150 faces inward. More preferably, the outer surface of the inner pot may also have the concave-convex structure 111 and the coating 150, and the surface layer 120 of the coating 150 faces outward. According to the inner pot of the present application, it is made of the composite sheet of the first aspect, and therefore has a technical effect similar to that of the composite sheet of the first aspect.

[0152] The third aspect of the present application also provides a cooking utensil. The cooking utensil includes a pot body and a cover body, and the cover body can be connected to the pot body. The pot body is basically in the shape of a rounded rectangular parallelepiped and has a cylindrical inner pot storage portion, and the inner pot can be freely placed in the inner pot storage portion or taken out from the inner pot storage portion to facilitate the cleaning of the inner pot. The inner pot is usually made of metal material and has a circular opening on the upper surface for holding materials to be heated, such as rice, soup, etc. The pot body may include a heating device for heating the inner pot.

[0153] The cover has a shape that is substantially corresponding to the pot body. The cover can be opened and closed on the pot body. Specifically, it is pivotally connected to the pot body via a pivot shaft and can freely pivot between a closed position and an open position relative to the pot body around a pivot axis where the pivot shaft is located, so as to facilitate the closing and opening of the pot body. When the cover is closed on the pot body, it covers the inner pot and forms a cooking space between the inner pot and the cover. The cooking utensil according to the present application has the inner pot of the second aspect above, and thus has a technical effect similar to that of the inner pot of the second aspect above.

[0154] The fourth aspect of the present application also provides a method for manufacturing a composite sheet. Fig.12 and Fig.13 As shown, the method for manufacturing the composite sheet includes a metal substrate preparation step S1 and a physical vapor deposition step S2.

[0155] The step S1 of preparing the metal substrate includes a step of forming a concavo-convex structure: preparing a plurality of concavo-convex structures 111 arranged at intervals on the surface of the metal substrate 110. The concavo-convex structures 111 are convexities or concavities. After the step of forming the concavo-convex structures 111, the metal substrate 110 is placed in a physical vapor deposition device.

[0156] The physical vapor deposition step S2 is specifically to deposit the coating film 150 at least on the concavo-convex structure 111 of the metal substrate 110. The physical vapor deposition step S2 includes a surface layer deposition step S23: growing the surface layer 120 of the coating film 150 into a columnar nanocrystalline structure by physical vapor deposition.

[0157] According to the present application, the combination of the micron-scale concave-convex structure of the composite sheet prepared by this manufacturing method and the columnar nanocrystal PVD coating can make the composite sheet have good non-stick properties, hydrophobic properties and easy-to-clean characteristics without setting a special non-stick coating, and also have high hardness and scratch resistance. The columnar nanocrystal structure can be directly formed on the surface of the metal substrate through physical vapor deposition without the need for additional steps.

[0158] Before the step of forming the concavo-convex structure, the metal substrate 110 may be cleaned, degreased and deoiled.

[0159] Specifically, the concave-convex structure 111 can be prepared by a rolling process, a roll-to-roll micro-imprinting process, a chemical etching process, a laser etching process or an ultraviolet lithography process. In this embodiment, the concave-convex structure 111 is prepared on the surface of the metal substrate 110 by a laser etching process, and specifically, the metal substrate 110 can be moved or the laser can be moved. The laser power density is set to 10 6 -10 7 W / cm 2, the laser spot size is 10-100μm, the scanning speed is 5-20mm / s, and the pulse frequency is 10-100KHz.

[0160] Furthermore, the step of preparing the metal substrate S1 further includes a polishing step, in which the metal substrate 110 is polished. The polishing step is located after the step of forming the concave-convex structure, so that the surface roughness of the metal substrate 110 is 0.1-3 μm. Since the surface of the metal substrate 110 has a concave-convex structure 111, it is difficult for a conventional polishing process to achieve the desired effect. Therefore, a plasma polishing process, a magnetic fluid polishing process, or a chemical polishing process can be used to polish the metal substrate 110. In this embodiment, a plasma polishing process is used to polish the concave-convex structure 111, and the density of the plasma is set to 1×10 11 -5×10 11 cm 3 , polishing power is 50-200W, gas flow rate is 10-50sccm, and polishing time is 5-30min.

[0161] After the polishing step, the surface of the metal substrate 110 may be cleaned and dried.

[0162] Specifically, physical vapor deposition may be performed by magnetron sputtering, arc ion plating, etc. In this embodiment, the arc ion plating process is used to deposit the coating 150 at least on the concavo-convex structure 111 of the metal substrate 110 .

[0163] More specifically, if Fig.10 and Fig.11 As shown, a rotating frame 12, a first metal target 13 and a second metal target 14 different from the first metal target 13 are provided in a deposition furnace 11 of the physical vapor deposition device 10. The first metal target 13 and the second metal target 14 are arranged at intervals around the rotation axis of the rotating frame 12. The metal elements of the first metal target 13 and the second metal target 14 are selected from titanium, chromium or zirconium. For example, the first metal target 13 can be a titanium target, and the second metal target 14 can be a chromium target. The physical vapor deposition device 10 also has a carbon source and a nitrogen source, wherein the carbon source is preferably acetylene gas, and the nitrogen source is preferably nitrogen.

[0164] The step S1 of preparing the metal substrate includes: placing the metal substrate 110 on a rotating frame and making the surface of the metal substrate 110 to be deposited face away from the rotation axis.

[0165] The step S23 of depositing the surface layer also includes: opening one of the first metal target 13 and the second metal target 14, opening the carbon source and the nitrogen source, and depositing the surface layer 120 on the surface to be deposited of the metal substrate 110. The metal element of the first metal target 13 or the second metal target 14 reacts with the carbon source and the nitrogen source to form the surface layer 120. Specifically, the step S23 of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 10-30min to control the thickness of the surface layer 120 to be 100-600nm.

[0166] The physical vapor deposition step also includes a transition layer deposition step S22. The transition layer deposition step S22 is located before the surface layer deposition step S23, and the transition layer deposition step S22 includes: opening the first metal target 13 and the second metal target 14, and alternately depositing the first transition layer 131 and the second transition layer 132 on the surface to be deposited of the metal substrate 110 by rotation, wherein the metal elements of the first metal target 13 react with the carbon source and the nitrogen source to form the first transition layer 131, and the metal elements of the second metal target 14 react with the carbon source and the nitrogen source to form the second transition layer 132. According to the above process, the metal substrate 110 is alternately covered by the coating materials produced by the first metal target 13 and the second metal target 14 by rotation, so that the alternatingly stacked first transition layer 131 and the second transition layer 132 can be efficiently formed. Specifically, the step S22 of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer 130 to be 300-1000nm.

[0167] The physical vapor deposition step also includes a bottom layer deposition step S21. The bottom layer deposition step S21 is located before the transition layer deposition step S22. The bottom layer deposition step S21 includes: opening the first metal target 13 and / or the second metal target 14, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace 11, and depositing the metal bottom layer 140 on the surface to be deposited of the metal substrate 110. This solution can use the same PVD equipment to deposit the metal bottom layer 140. Specifically, the bottom layer deposition step S21 also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate 110 during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer 140 to be 100-500nm.

[0168] In the physical vapor deposition step S2 , the rotation speed of the rotating frame 12 is set to 0.5-3 rpm to more effectively control the thickness of the coating film 150 and make the thickness distribution of the coating film 150 uniform.

[0169] The processes described in all the above preferred embodiments are only examples. Unless adverse effects occur, various processing operations can be performed in a sequence different from the sequence of the above processes. The sequence of steps in the above processes can also be increased, merged or deleted according to actual needs.

[0170] Unless otherwise defined, the technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein are only for describing specific implementation purposes and are not intended to limit the present application. The features described herein in one embodiment may be applied to another embodiment individually or in combination with other features, unless the feature is not applicable or otherwise specified in the other embodiment.

[0171] The present application has been illustrated through the above-mentioned embodiments, but it should be understood that the above-mentioned embodiments are only for the purpose of example and explanation, and the present application is not limited to the above-mentioned embodiments. According to the teachings of the present application, more variations and modifications can be made, and these variations and modifications all fall within the scope of protection claimed by the present application.

Claims

1. A composite sheet, characterized in that: include: A metal substrate, wherein the surface of the metal substrate has a plurality of concave-convex structures arranged at intervals, wherein the concave-convex structures are convexities or concavities; The coating is attached to the surface of the metal substrate by physical vapor deposition and covers the concave-convex structure, wherein the coating comprises a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.

2. The composite sheet according to claim 1, characterized in that: The plurality of concave-convex structures are uniformly arranged at a first preset distance along a first direction, and the plurality of concave-convex structures are uniformly arranged at a first preset distance along a second direction perpendicular to the first direction, so as to form a concave-convex structure array.

3. The composite sheet according to claim 1, characterized in that: The multiple concave-convex structures are arranged into concave-convex units with a specific shape, the multiple concave-convex units are evenly arranged at a second preset distance along a first direction, and the multiple concave-convex units are evenly arranged at a second preset distance along a second direction perpendicular to the first direction to form a concave-convex unit array.

4. The composite sheet according to claim 3, characterized in that: The specific shape of the concave-convex unit is a solid shape composed of a plurality of concave-convex structures evenly arranged at a first preset distance; or The specific shape of the concave-convex unit is configured as a hollow shape formed by a plurality of concave-convex structures being evenly arranged at a first preset distance.

5. The composite sheet according to claim 4, characterized in that: The second preset distance is greater than the first preset distance.

6. The composite sheet according to claim 1, characterized in that: The surface roughness of the surface layer is 0.1-3 μm, and the surface roughness of the metal substrate is 0.1-3 μm; and / or The friction coefficient of the surface layer is 0.05-0.4, and the contact angle of water on the surface of the surface layer is 80-110°.

7. The composite sheet according to claim 1, characterized in that: The radial dimension of the concavo-convex structure is 10-100 μm; and / or The height dimension of the concavo-convex structure is 5-50 μm.

8. The composite sheet according to claim 1, characterized in that: The columnar nanocrystal structure in the surface layer has multiple grains growing in a columnar shape, and the side surfaces of the multiple grains are attached to each other. When the surface layer is at a predetermined thickness, the top ends of the grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.

9. The composite sheet according to claim 8, characterized in that: The radial size of the grains is 20-80 nm; and / or The predetermined thickness of the surface layer is 100-600 nm.

10. The composite sheet according to claim 2 or 4, characterized in that: The first preset distance is 10-1000 μm.

11. The composite sheet according to any one of claims 1 to 9, characterized in that: The coating further includes a transition layer, the surface layer is attached to the transition layer, the transition layer includes a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked.

12. The composite sheet according to claim 11, characterized in that The coating also includes a bottom layer, the bottom layer is attached to the surface of the metal substrate, the transition layer is attached to the bottom layer, and the bottom layer is a metal layer.

13. The composite sheet according to claim 12, characterized in that: The thickness of the first transition layer is 10-50 nm, the thickness of the second transition layer is 10-50 nm, and the total thickness of the transition layers is 300-1000 nm; and / or The thickness of the bottom layer is 100-500 nm; and / or The total thickness of the coating is 700-2000nm.

14. The composite sheet according to any one of claims 1 to 9, characterized in that: The surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.

15. The composite sheet according to any one of claims 1 to 9, characterized in that: The surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer.

16. The composite sheet according to claim 15, characterized in that Amorphous copper encapsulates the grains of the columnar nanocrystalline structure.

17. The composite sheet according to claim 11, characterized in that: The first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is different from the first transition layer.

18. The composite sheet according to claim 12, characterized in that: The bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.

19. A liner, characterized in that: The liner comprises a composite sheet according to any one of claims 1-18.

20. A cooking utensil, characterized in that: include: A pot body, wherein the pot body is provided with the inner pot according to claim 19; The cover body is openably and closably arranged on the pot body. When the cover body covers the pot body, a cooking space is formed between the cover body and the inner pot.

21. A method for manufacturing a composite sheet, characterized in that: The method for manufacturing the composite sheet comprises: The step of preparing a metal substrate comprises: The step of forming a concavo-convex structure is as follows: a plurality of concavo-convex structures are prepared on the surface of the metal substrate and are arranged at intervals, wherein the concavo-convex structures are convex or concave. placing the metal substrate in a physical vapor deposition apparatus; The physical vapor deposition step is to deposit a coating at least on the concave-convex structure of the metal substrate, and the physical vapor deposition step includes a surface deposition step: the surface layer of the coating is grown into a columnar nanocrystalline structure by physical vapor deposition.

22. The manufacturing method according to claim 21, characterized in that: The concave-convex structure is prepared by a rolling process, a roll-to-roll micro-imprinting process, a chemical etching process, a laser etching process or an ultraviolet lithography process.

23. The manufacturing method according to claim 22, characterized in that: The step of forming the concave-convex structure also includes: using the laser etching process to prepare the concave-convex structure on the surface of the metal substrate, setting the laser power density to 10 6 -10 7 W / cm 2 , the laser spot size is 10-100μm, the scanning speed is 5-20mm / s, and the pulse frequency is 10-100KHz.

24. The manufacturing method according to claim 21, characterized in that: The step of preparing the metal substrate further comprises a polishing step after the step of forming the concavo-convex structure, wherein the metal substrate is polished so that the surface roughness of the metal substrate is 0.1-3 μm.

25. The manufacturing method according to claim 24, characterized in that: The metal substrate is polished by using a plasma polishing process, a magnetic fluid polishing process or a chemical polishing process.

26. The manufacturing method according to claim 25, characterized in that: The polishing step includes: polishing the concave-convex structure using the plasma polishing process, setting the plasma density to 1×10 11 -5×10 11 cm 3 , polishing power is 50-200W, gas flow rate is 10-50sccm, and polishing time is 5-30min.

27. The manufacturing method according to any one of claims 21 to 26, characterized in that: The deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source; The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis; The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening the carbon source and the nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.

28. The manufacturing method according to claim 27, characterized in that: The physical vapor deposition step also includes a transition layer deposition step, which is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form the first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form the second transition layer.

29. The manufacturing method according to claim 28, characterized in that: The physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step. The bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.

30. The manufacturing method according to claim 27, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to 100-600nm.

31. The manufacturing method according to claim 28, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to 300-1000nm.

32. The manufacturing method according to claim 29, characterized in that: The deposition of the bottom layer also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to 100-500nm.

Citation Information

Cited By

  • Metal cooking utensil and preparation method thereof

    CN120616295A